Abnormal Movement Following Transcobalamin II Deficiency Treatment Responding to Clonazepam: A Case Report - AlFaris, Haya Salman; AlJefri, Abdullah Hussain; Alsowat, Daad Khalaf (Journal of Pediatric Neurology, 2022)
Transcobalamin II (TCII) is a transporter protein that facilitates cobalamin release from the bloodstream to the cell. Deficiency in TCII is an autosomal recessive disorder caused by a mutation in the TCN2 gene. Treatment with intramuscular injection of hydroxocobalamin is greatly effective in improving the symptoms of this disorder. However, abnormal involuntary movements can occur and have been reported in patients with cobalamin deficiency caused by nutritional deficiency. Though, it is rarely associated with the treatment of hereditary TCII deficiency. Here, we report such a case, aiming to alert practitioners treating hereditary TCII deficiency. A 2-year-old boy born to a consanguineous parents presented with failure to thrive, recurrent infection, and pancytopenia. His condition deteriorated rapidly, and his investigation was remarkable for pancytopenia, elevated methylmalonic acid, and myelodysplastic changes in the bone marrow. A flash whole-exome sequence confirmed the diagnosis of TCII deficiency. The patient began treatment with IM hydroxocobalamin, and on the second day, he developed an abnormal involuntary movement that was abated by clonazepam. Abnormal nonepileptic movements following IM hydroxocobalamin in a patient with TCII deficiency shows a remarkable response to clonazepam.
Keywords: transcobalamin II deficiency; clonazepam; tremors; erratic myoclonus